Effects of Work-Life Balance and Job Stress on Job Satisfaction During the Covid-19 Pandemic at Karawang Hospital - Mohamad RIZAN; Farah CHALIDA HANOUM (Communications of International Proceedings, 2022)
Background: Work-life balance for nurses is low, work stress for nurses is high, and job satisfaction for nurses in private hospitals in Karawang is low. Novelty: Research on job satisfaction with the addition of independent variables work-life balance and work stress in health workers with a background in the health sector is still rarely found in Karawang private hospitals, where the existing literature has not been explained. The purpose of this study was to see how the effect of work-life balance on job satisfaction in nurses, how the effect of job stress on job satisfaction in nurses, and how the effect of work-life balance and work stress on job satisfaction in nurses. Method: the sample in this study was 200 respondents. The respondents were female nurses in a private hospital in Karawang. The hypothesis was tested by structural equation modeling (SEM) with Lisrel 88.0 software. Results: showed that the work-life balance variable positively affected job satisfaction by 0.454, and the t-count value was 6.585 (Significant: count > 1.96). These results explain that work-life balance positively and significantly affects job satisfaction. These results indicate that H1 is accepted, which suggests that work-life balance can increase job satisfaction. Then the impact of work stress on job satisfaction is -0.433, and the t value is -6.432 (Significant: count > 1.96). These results explain that work stress negatively and significantly affects job satisfaction. These results indicate that H2 is accepted, which suggests that job stress can reduce job satisfaction. Implications: work-life balance and work stress have an essential role in determining the increase and decrease in job satisfaction of nurses in private hospitals in Karawang, West Java province. This research study implies that the hospital can improve work-life balance and reduce the level of work stress experienced by nurses in private hospitals in Karawang, West Java province, so that nurse job satisfaction can continue to increase.
Keywords: Work-life balance; Job Stress; Job Satisfaction